The impact of location on crop choice and rural livelihood: evidences from villages in Northern Ethiopia - Seid Nuru; Holger Seebens (University of Bonn, Center for Development Research (ZEF), 2008)
This paper attempts to demonstrate how location of an agricultural economic activity in relation to urban centers determines households' decision to allot their agricultural land to the production of either staple crop or a high value but risky cash crop. Analyzing household data from villages in North Eastern Ethiopia, we find that proximity to urban centers, access to road, and education along with other factors determine the crop choice in favor of the production of high value crops. Crop choices further significantly predict levels of per capita income across villages where the farthest with no access to road are the poorest. – – In dieser Arbeit wird gezeigt, dass die Entfernung eines Anbaugebiets zu Ballungsgebieten Einfluss nimmt auf die Entscheidung eines Haushalts darüber, ob eher minder- oder hochwertige aber risikoreiche Pflanzen angebaut werden. Bei der Analyse von Daten aus Nordost-Äthiopien, konnte festgestellt werden, dass die Nähe zu Ballungsgebieten und der Zugang zu befestigten Straßen zusammen mit weiteren Faktoren Einfluss auf die Entscheidung über die anzubauenden Nutzpflanzen nimmt. Geringe Entfernung und Zugang zu Straßen beeinflussen dabei die Entscheidung zugunsten des Anbaus von hochwertigen Nutzpflanzen. Die Wahl des Pflanzenportfolios hat ebenso einen Einfluss auf das Pro-Kopf-Einkommen in den untersuchten Dörfern, wobei die entfernt gelegenen Dörfer ohne Zugang zu befestigten Straßen die ärmsten sind.
Keywords: 330